2018
DOI: 10.3390/polym10101123
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Pore Structure in Polyvinylidene Fluoride (PVDF)/Graphene Composite Membrane Probed by Electrochemical Impedance Spectroscopy

Abstract: In this paper, graphene was introduced in the PVDF to improve the thermal stability of the pore structure, which is the key feature for the membrane applied for the thermo-osmotic energy conversion (TOEC) process. The PVDF/graphene composite membranes were characterized by a scanning electron microscopy (SEM), a water contact angle measurement, and electrochemical impedance spectroscopy (EIS). It was found that the composite membranes exhibited improved surface hydrophobicity. Moreover, the pores in pure PVDF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Therefore, the observation of GO membrane morphology by SEM, TEM, and AFM, which are typically operated in a vacuum environment, can hardly establish the correlation between the membrane structure and membrane performances. Other techniques, for example, electrochemical impedance microscopy (EIS) [ 9 ], has showed its advantage in providing more information of the membrane structures in such cases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the observation of GO membrane morphology by SEM, TEM, and AFM, which are typically operated in a vacuum environment, can hardly establish the correlation between the membrane structure and membrane performances. Other techniques, for example, electrochemical impedance microscopy (EIS) [ 9 ], has showed its advantage in providing more information of the membrane structures in such cases.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS), as an economic and non-invasive characterization technique, can be potentially utilized to study the membrane structures [ 9 , 17 , 18 ], membrane fouling [ 19 , 20 ], and internal concentration polarization (ICP) [ 21 ]. The electrochemical relaxations are related to the intrinsic properties of the studied systems; thus, it can reveal structural features such as structural layers, pore structures, etc., through suitable equivalent circuit modeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macroscopic three-dimensional (3D) graphene structures have been obtained by interconnecting 2D graphene sheets that have been successfully synthesized via various methods. In addition to the inherent properties of 2D graphene, 3D graphene structures present large accessible surface areas, excellent mechanical strength and great flexibility because of their porous interconnected network structures [1,2,3,4]. Therefore, 3D graphene is widely studied in the gas adsorption and supercapacitor fields.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) is a noninvasive tool that is extensively used to study the chemical, electrochemical, interfacial structural, as well as ion-transport properties of different types of membranes. , This alternating-current-based technique allows the differentiation between the individual contributions of different phenomena occurring at the membrane surface and not accessible by direct-current-based measurements . Published EIS studies on graphene–polymer hybrids are scarce, and the EIS of 3D LIG has not yet been reported. Here we incorporated LIG on synthesized (see the SI) ion-exchangeable membranes (sulfonated poly­(ether sulfone) (SPES)) or nonporous nonionexchangeable membranes (poly­(ether sulfone) (PES)) and used EIS to explore the electrical properties of the hybrid membranes (SPES–LIG or PES–LIG) during cation (Na + , K + , Mg 2+ , Ca 2+ ) transport.…”
mentioning
confidence: 99%